1996
DOI: 10.1111/j.1525-1446.1996.tb00213.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Public Health Nursing Services: Relationship to Adequacy of Prenatal Care and Infant Outcome

Abstract: Timing of initial public health nurse contact and number of nurse contacts were examined for their relationship to adequacy of prenatal physician care, infant birthweight, and gestational age. Three historical cohort groups were drawn from three downstate Illinois counties: 1) public health nursing clients (N = 506); 2) Women, Infant, and Children Nutrition Program clients (N = 314); and 3) clients receiving neither of these services (N = 403). Data were obtained from local health department records and a stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…This evaluation showed a strong association between early PHN contact and increased physician prenatal services, as was noted in another research study ( Baldwin & Chen, 1996). The timing of initial PHN contact coincided with the trimester of access to prenatal care, which was markedly improved in the second pregnancy.…”
Section: Discussion Of Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…This evaluation showed a strong association between early PHN contact and increased physician prenatal services, as was noted in another research study ( Baldwin & Chen, 1996). The timing of initial PHN contact coincided with the trimester of access to prenatal care, which was markedly improved in the second pregnancy.…”
Section: Discussion Of Resultssupporting
confidence: 84%
“…Numerous research studies have shown that early and adequate prenatal care can dramatically improve birthweight outcomes and infant health outcomes ( Poland et al, 1990; Goldfarb et al, 1991; Hulsey, Patrick, Alexander, & Ebeling, 1991; Fink, Yano, & Goya, 1992). Baldwin and Chen (1996) showed significant correlation between the timing of initial public health nursing contact and adequacy of prenatal physician contact.…”
Section: Literature Reviewmentioning
confidence: 97%
“…A study of intervention methods most preferred by mothers from Central America found that home visits by a PHN and home visits by a lay health worker were preferred over other current intervention methods including the use of videos, clinic group presentations, and brochures (Gaffney, 1995). Baldwin and Chen (1996) recommended that greater emphasis must be placed on outreach programs using lay health workers in conjunction with PHN case‐finding to bolster early initiation of PHN prenatal services.…”
Section: Discussionmentioning
confidence: 99%
“…Initiation of PHN services was examined for two reasons. First, Baldwin and Chen (1996) determined that, except for their own work, no studies have examined this variable in relation to other prenatal risk factors or infant health outcomes. Since initial PHN services include important anticipatory guidance including smoking cessation, discontinuing alcohol and drug use, and following safe sex and good nutrition practices that have impact on prenatal behaviors and LBW outcomes, this omission in clinical research is significant.…”
Section: Methodsmentioning
confidence: 99%